COMPARATIVO DE DIFERENTES GRUPOS DE FUNGICIDAS NO CONTROLE DE DOENÇAS DO FEIJOEIRO - Jasper, Mônica (2010)
Beans are a staple food for the Brazilian. The average current consumption of 12.7 kg of beans is Brazilian per year. The diseases are among the most important factors associated with low productivity of common bean in Brazil and could considerably reduce the production of this crop. Among the diseases are highlighted anthracnose (Colletotrichum lindemuthianum), rust (Uromyces phaseoli var. Typica), angular leaf spot (Phaeoisariopsis griseola) and powdery mildew (Erysiphe polygoni). The most effective disease control is obtained by summation of control measures available and never an isolated practice. In this context, chemical control, when well managed, has been an important tool for the production process, especially when environmental conditions are favorable for disease development. The objective of this experiment was to evaluate the efficiency of different groups of fungicides in the management of major diseases of common bean, using the cultivar IPR 88 - Uirapuru, black beans, Group II of indeterminate habit. The experiment was conducted in the city of Ponta Grossa, PR, School Farm Capon of Oz, "owned by the State University of Ponta Grossa. By analyzing the results of this experiment we can conclude: for control of anthracnose, the best treatments were chlorothalonil, pyraclostrobin, and tebuconazole fentin hydroxide with 3 applications. With respect to angular leaf spot, strobilurins were less efficient. The treatments were more effective in controlling tebuconazole, Fentin hydroxide, metconazole, difenoconazole (all three applications) and chlorothalonil. For rust, the best treatments were azoxystrobin, pyraclostrobin, and tebuconazole metconazole. Fentin hydroxide and chlorothalonil were less efficient in controlling the disease, regardless of the number of applications.Assessing the mildew, it is noted that the best treatments with chlorothalonil, regardless of the number of applications. The other fungicides were superior when applied 3 times. The use of chlorothalonil proved effective in controlling anthracnose, angular leaf spot and powdery mildew, not showing satisfactory control against rust.Regarding the percentage of grains patients, all treatments had lower percentages than the control, except with the difeconazol 2 applications. When assessing the weight of thousand grain weight, it was evident that the treatment with three applications Fentin hydroxide, pyraclostrobin, and tebuconazole metconazole distinguished in the experiment, as well as treatments with chlorothalonil. As regards productivity, the highest increase occurred in treatments with chlorothalonil, no statistical differences between treatments with pyraclostrobin, tebuconazole and fentin hydroxide.